Frequency up-conversion technique for radio over fiber (ROF) remote antenna unit configuration - Mohamed, N. (2012)
This work involves in transmitting of intermediate frequency (IF) signal over fiber utilizing photonics frequency conversion, which, the main focus is the development of optical front-end receiver. The system uses photodiode and heterojunction bipolar transistor (HBT) to detect and up-convert the received IF modulated optical signal. The photodiode (PD) and HBT are very useful devices for photonics frequency conversion technique with high internal gain and frequency up conversion of optical signal. Through simulation, the optimum device parameters and characteristics were determined. The system was implemented to detect a 0.4 GHz of IF carriers signal and up-converted to 3.4 GHz of radio frequency (RF) signal. The optimum conversion gain that has been obtained from the measurement and simulation were about -11 dB and -8 dB, respectively, at V BE = 0.7 V, P LO = 4 dBm, and -25 dBm of IF optical input power. The system has been practically demonstrated and shown to agree reasonably well with both the theory and simulation. This article also refers to some recent patents on frequency conversion techniq.